Lumbar disc herniation is an independent predictor of plaque burden in the patients with unstable angina - Wang, Yongchao; Ge, Junhua; Xu, Hao; Li, Jian (Frontiers in Cardiovascular Medicine, 2024)
Objective Assessing the impact of lumbar disc herniation (LDH) on the plaque burden of coronary atherosclerosis is our objective. Methods In this study, a total of 212 patients (age 46–80 years) with unstable angina (UA) who underwent coronary angiography (CAG) in our hospital from January 2018 to July 2022 due to UA were included. Patients were divided into LDH group (n = 106) and no LDH group (n = 106). Gensini scores were calculated to assess the plaque burden of coronary. Logistic analysis was used to examine potential risk variables linked to the Gensini score. The association between lumbar disc lesions grading and coronary plaque burden was analysed by Spearman's correlation test. LDH patients with higher plaque burden (n = 56) were further divided into evolocumab treatment group (n = 28) and conventional treatment group (n = 28). Cox regression analysis were performed. Results Patients with LDH had higher Gensini scores (P < 0.01) and triglyceride (TG) levels (P = 0.04), but HDL-C (P = 0.01) levels were lower. LDH was found to be an independent risk factor for higher Gensini scores (OR = 2.38, P < 0.01) by logistic analysis. The Spearman's correlation test suggested that the degree of lumbar disc lesions was related to the Gensini score and the level of blood lipid. Cox regression analysis showed that evolocumab treatment could significantly reduce the composite MACE events (cardiac death, nonfatal myocardial infarction, nonfatal stroke, and readmission due to angina) (HR = 0.26, P = 0.04) in higher coronary plaque burden patients. Conclusion LDH is an independent risk factor for the higher coronary plaque burden. Evolocumab treatment significantly reduced the occurrence of cardiovascular events in LDH patients with higher plaque burden. Additionally, our data indicate that LDH is associated with increased blood lipid, which may contribute to the development of plaque burden.